Pengaruh Pelaksanaan Peer Learning Terhadap Peningkatan Pengetahuan Mahasiswa D3 Keperawatan Tentang Konsep Keperawatan Medikal Bedah - Papo Bage, Veronika; Elisabeth Monteiro (Journal of Pubnursing Sciences, 2023)
This research aims to instill the influence of peer learning method training on increasing the knowledge of students in the STIKes Mayapada Nursing Diploma III Study Program. The research design used was a quasi-experimental design with an intervention group that took part in peer learning training and a control group that did not take part in similar training. The research population was all students in semesters 3, 5, and 6, with a sample of 40 students selected randomly. Data was collected through training evaluations and knowledge tests before and after training. The results of the data analysis showed that the intervention group experienced a significant increase in knowledge (p < 0.05), while the control group did not show a significant change. The implication is that peer learning training can increase students' knowledge of Nursing, support the concept of inclusive education, and prepare students to face the demands of the ever-growing homicidal profession. This research makes an important contribution to understanding the benefits of peer learning in the context of protection education.